European Summit on the Prevention and Self‐Management of Chronic Respiratory Diseases: report of the European Union Parliament Summit (29 March 2017). Issue 1 (27th December 2017) - Hellings, Peter W.; Borrelli, David; Pietikainen, Sirpa; Agache, Ioana; Akdis, Cezmi; Bachert, Claus; Bewick, Michael; Botjes, Erna; Constantinidis, Jannis; Fokkens, Wytske; Haahtela, Tari; Hopkins, Claire; et al.
Abstract: On March 29, 2017, a European Summit on the Prevention and Self‐Management of Chronic Respiratory Diseases (CRD) was organized by the European Forum for Research and Education in Allergy and Airway Diseases. The event took place in the European Parliament of Brussels and was hosted by MEP David Borrelli and MEP Sirpa Pietikainen. The aim of the Summit was to correspond to the needs of the European Commission and of patients suffering from CRD to join forces in Europe for the prevention and self‐management. Delegates of the European Rhinologic Society, European Respiratory Society, European Academy of Allergy and Clinical Immunology, European Academy of Paediatrics, and European Patients Organization EFA all lectured on their vision and action plan to join forces in achieving adequate prevention and self‐management of CRD in the context of Precision Medicine. Recent data highlight the preventive capacity of education on optimal care pathways for CRD. Self‐management and patient empowerment can be achieved by novel educational on‐line materials and by novel mobile health tools enabling patients and doctors to monitor and optimally treat CRDs based on the level of control. This report summarizes the contributions of the representatives of different European academic stakeholders in the field of CRD.